2017
DOI: 10.3788/col201715.030003
|View full text |Cite
|
Sign up to set email alerts
|

Linear and angular momenta in tightly focused vortex segmented beams of light (Invited Paper)

Abstract: We investigate the linear momentum density of light, which can be decomposed into spin and orbital parts, in the complex three-dimensional field distributions of tightly focused vortex segmented beams. The chosen angular spectrum exhibits two spatially separated vortices of opposite charge and orthogonal circular polarization to generate phase vortices in a meridional plane of observation. In the vicinity of those vortices, regions of negative orbital linear momentum occur. Besides these phase vortices, the oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Thus, the presence of areas in which the total energy flux is directed towards the radiation source can be explained by the fact that the spin flux directed towards the source exceeds in absolute value the orbital energy flux [27]. A negative orbital energy flux was observed in [26]. In an earlier paper [18], we found that regions of reverse energy flux arise not only in the focus plane, but also in planes close to it.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…Thus, the presence of areas in which the total energy flux is directed towards the radiation source can be explained by the fact that the spin flux directed towards the source exceeds in absolute value the orbital energy flux [27]. A negative orbital energy flux was observed in [26]. In an earlier paper [18], we found that regions of reverse energy flux arise not only in the focus plane, but also in planes close to it.…”
Section: Introductionmentioning
confidence: 57%
“…The study in [17] showed that in the Weber modes, the projection of the Poynting vector onto the optical axis takes negative values. The energy flux is the sum of two fluxes: the spin flux and the orbital energy flux [25,26]. Thus, the presence of areas in which the total energy flux is directed towards the radiation source can be explained by the fact that the spin flux directed towards the source exceeds in absolute value the orbital energy flux [27].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these dynamical characteristics are crucial for understanding the physics behind light-matter interactions with small particles. In the last decade, several theoretical and experimental studies of the dynamical characteristics of various focused beams have been reported, including the fundamental Gaussian beam [31,32], Laguerre-Gaussian (LG) beam [33][34][35], Bessel-Gaussian (BG) beam [36][37][38][39], double-vortex beam [13,14], and other structured light beams [40][41][42][43][44][45][46][47][48]. The LG beam is one of the most well-studied types of structured light beams, both theoretically and experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Optical cage is a specific kind of optical field that has a dark region surrounded by higher intensity. Owing to its intriguing distribution, an optical cage can be applicable to a multitude of areas, such as optical trapping and manipulation [1][2][3][4][5][6] and optical imaging [7][8][9] . Consequently, the generation of an optical cage has attracted much attention from researchers.…”
mentioning
confidence: 99%